2004
DOI: 10.1111/j.1360-0443.2004.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based screening and brief intervention for hazardous drinking: a double‐blind randomized controlled trial

Abstract: e-SBI reduced hazardous drinking among university students, to an extent similar to that found for practitioner-delivered brief interventions in the general population. e-SBI offers promise as a strategy to reduce alcohol-related harm in a way that is non-intrusive, appealing to the target group, and capable of being incorporated into primary care. Research is required to replicate the findings, to determine the duration of intervention effects, and to investigate the mechanisms by which the intervention opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
217
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 265 publications
(231 citation statements)
references
References 23 publications
8
217
2
4
Order By: Relevance
“…Second, information in this study was obtained through self-report. Although self-report potentially leads to biased or distorted reporting, self-reported alcohol use is common practice in studies evaluating computerized interventions (Bersamin, Paschall, Fearnow-Kenney, & Wyrick, 2007;Chiauzzi, Green, Lord, Thum, & Goldstein, 2005;Doumas & Hannah, 2008;Doumas & Haustveit, in press;Kypri et al, 2004;Neighbors et al, 2004;Walters et al, 2007). Additionally, research indicates that the reliability of self-report is adequate (Marlatt et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Second, information in this study was obtained through self-report. Although self-report potentially leads to biased or distorted reporting, self-reported alcohol use is common practice in studies evaluating computerized interventions (Bersamin, Paschall, Fearnow-Kenney, & Wyrick, 2007;Chiauzzi, Green, Lord, Thum, & Goldstein, 2005;Doumas & Hannah, 2008;Doumas & Haustveit, in press;Kypri et al, 2004;Neighbors et al, 2004;Walters et al, 2007). Additionally, research indicates that the reliability of self-report is adequate (Marlatt et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In 5 trials rated as low to moderate risk of bias in students (37,48,49,52), e-interventions resulted in no statistically significant reduction in binge drinking (MD, −0.1 episodes [CI, −0.6 to 0.4]) at 6-month follow-up. Effect sizes had moderate heterogeneity (Q = 8.8; P = 0.066; I 2 = 55%); 1 trial rated as low risk of bias that studied human support reported significant effects (44).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…In a study by Kypri et al [16], computerized alcohol interventions performed as well as practitioner-delivered brief interventions.…”
Section: Introductionmentioning
confidence: 99%